Experimental investigation of temperature effect on hydrodynamic characteristics of natural cavitation in rotational supercavitating evaporator for desalination. (August 2021) - Zheng, Zhi-Ying; Wang, Lu; Wei, Tong-Zhou; Cai, Wei-Hua; Li, Hui; Yao, Li-Ming; Li, Feng-Chen
Abstract: Increasing temperature is proposed to improve the performance of Rotational Supercavitating Evaporator (RSCE, a novel supercavitation-based desalination device). In order to investigate the temperature effect on the hydrodynamic characteristics of RSCE, visualization experiments are conducted on cavitating flows at different water temperatures (25–50 °C) in RSCE under different rotational speeds (up to 4000 r/min). Then the thermodynamic effect of cavitation in the water at different temperatures is evaluated to obtain the temperature range suitable for the operation of RSCE. Results show that the spatiotemporal evolutions of cavitation at different water temperatures are similar and the cavitation intensity increases with increasing temperature. Combining the present experimental results with revisits to the published results, four criteria are put forward to evaluate the thermodynamic effect of cavitation, including the variation of dimensionless supercavity length with cavitation number, the variation of incipient cavitation number with temperature, the appearance of cavitation, and the threshold value of thermodynamic parameter Σ of order hundred. It can be deduced by these criteria that the thermodynamic effect of cavitation in the water is insignificant within the temperature range considered in the present work. Hence, the desalination performance of RSCE can be improved by increasing temperature within above temperature range. Highlights: Thermodynamic effect of cavitation in the water below 60 °C is insignificant. Four criteria for evaluating the thermodynamic effect of cavitation are proposed. Variation of cavity length with cavitation number is used for quantitative evaluation. Variation of incipient cavitation number is used to evaluate thermodynamic effect. Threshold value of thermodynamic parameter Σ is of order hundred.